Developmental Changes in the Roles of Patients and Families in Type 1 Diabetes Management - T. Markowitz, Jessica; C. Garvey, Katharine; M.B. Laffel, Lori (Current Diabetes Reviews, 2015)
Developmentally-tailored diabetes self-care education and support are integral parts of contemporary multidisciplinary T1D care. The patient with T1D must have the support of the family and the diabetes team to maintain the rigors of diabetes management, but the specific roles of patients and families with regard to daily diabetes tasks change considerably throughout the developmental span of early childhood, middle childhood/school-age years, and adolescence. This review provides a framework of key normative developmental issues for each of these developmental stages. Within this context, ideal family diabetes management is reviewed within each developmental stage and anticipated challenges that can arise during these stages and that can adversely impact diabetes management are presented. This paper also summarizes empirical evidence for specific intervention and care strategies to support optimal diabetes management across these stages in order to maximize opportunities for a successful transfer of diabetes management tasks from parents to maturing youth. Finally, the review provides an emphasis on approaches to promote family teamwork and adolescent diabetes self-care adherence as well as opportunities to use novel technology platforms as a means to support optimal diabetes management.
Keywords: transition